2022
DOI: 10.1007/s12144-022-02881-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Profiles of Addictive Smartphone Use: A Latent Profile Analysis

Abstract: Given that crucial psychological attributes of smartphone addiction have been studied in isolation from each other, we examined latent profiles of emotional distress (depression, stress, loneliness, and fear of missing out; i.e., FoMO); protective traits (self-control, mindfulness, grit); the behavioral inhibition system (BIS) and approach system (BAS; drive, reward responsiveness, and fun seeking) in relation to addictive smartphone use. We identified three distinctive profiles, using five fit statistics: AIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…The stress-buffering hypothesis posits that individuals with elevated levels of stress are more prone to exhibit heightened levels of sensation-seeking ( 82 ). One study found that people who scored high on aspects of the Behavioral Activation System (i.e., drive, reward responsiveness, fun seeking) were prone to smartphone addiction ( 23 ). Research on factors that contribute to addiction vulnerability indicates that sensation-seeking is a significant predictor of addictive behavior ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The stress-buffering hypothesis posits that individuals with elevated levels of stress are more prone to exhibit heightened levels of sensation-seeking ( 82 ). One study found that people who scored high on aspects of the Behavioral Activation System (i.e., drive, reward responsiveness, fun seeking) were prone to smartphone addiction ( 23 ). Research on factors that contribute to addiction vulnerability indicates that sensation-seeking is a significant predictor of addictive behavior ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…A latent profile analysis (LPA) was conducted using M plus 8.3 ( 23 ), identifying subgroups of participants (latent profiles) who exhibited comparable responses on the Bergen Social Media Addiction Scale (BSMAS) items (i.e., similar levels of risk for developing problematic social media use). Fit indices of 1–6 profiles were extracted for model comparison using the robust maximum likelihood (RML) estimation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grit is defined as a combination of two facets: consistency or sustained interests and persistent efforts (hereafter referred to as passion and perseverance) for long-term goals despite setbacks. 32 Mounting studies have revealed that grit is negatively associated with addictive behaviors in students (mainly college students), including mobile phone addiction, 33 , 34 social media addiction, 35 and IA. 36 , 37 Several recent studies have indicated that grit is negatively associated with media device addiction, 38 smartphone addiction, 39 and IA in adolescents.…”
Section: Introductionmentioning
confidence: 99%